Legalitas Cryptocurrency sebagai Alat Pembayaran Metaverse menurut Regulasi Perbankan Indonesia - Yosep (Jurnal Hukum Ekualitas, 2026)
This research aims to analyze the dualism of cryptocurrency status in Indonesian regulations and its implications for metaverse transactions. Using normative legal research methods with statutory and conceptual approaches, the study finds that cryptocurrency is recognized as a legal commodity (Bappebti Regulation No. 8/2021) but prohibited as a payment instrument (BI Regulation No. 18/40/PBI/2016 jo. Law No. 7/2011). This dualism creates legal uncertainty in metaverse transactions that are virtual and cross-border. The research recommends a three-zone approach: red zone (physical transactions prohibited), yellow zone (virtual transactions permitted with strict supervision), and green zone (trading as investment commodity). This approach balances protection of Rupiah's monetary sovereignty with national digital economy development, creating legal certainty for metaverse business actors without sacrificing Indonesia's payment system stability.